Zinc Oxide Supported onto Biogenic Silica from Gigantochloa atroviolacea Leaves: Preparation, Characterization and Antibacterial Activity - Sriwahyuni, Elsa; Prodjosantoso, Anti Kolonial; Sasmita, Dewi (Asian Journal of Chemistry, 2019)
Bamboo rod is a well known raw material utilized to make houses, papers, handicrafts, chopsticks and medicines. On the other hand, the utilzation of leaves, which are often considered as garbages, receive less attentions. Even though, bamboo leaves are good sources of SiO2 or silica. This work reports the preparation of zinc oxide (ZnO) supported onto biogenic silica (SiO2) from leaves of Gigantochloa atroviolacea, characterization and the antibacterial activities of ZnO@SiO2 against Staphylococcus epidermidis. The ZnO was supported onto biogenic SiO2 by using impregnation method of SiO2 in zinc salt [Zn(NO3)2·6H2O] solution. A combination XRD and SEM-EDX techniques were used to confirm the formation of ZnO on ZnO@SiO2. Investigations indicate that the as prepared ZnO@SiO2 revealed significant antibacterial activity against Staphylococcus epidermidis bacterial strain.